Brabant Biennale. - Frenken, Ton; Schampers, Karel; Van Abbemuseum, Eindhoven; De Beyerd, Breda; Kultureel Sentrum, Tilburg; Het Markiezenhof, Bergen op Zoom; 't Meyhuis Helmond (Eindhoven : ' Van Abbemuseum, 1980)
Berkulin, Arie ; de Bie, Jan ; Biezen, Hans ; Boender, Marius ; Coppens, Anton ; Daniels, René ; Elzinga, Pieter ; Gijsen, Jo ; Hocks, Teun ; Hollander, Paul den ; Horvers, Toine ; Kantelberg, Peter ; Koene, Peter ; Könings, Hans ; Kuipers, Paul ; Kuypers, Theo ; Kuys, Hans ; Loerakker, Bert ; Meyers, Matheu ; Silawanebessy, Lucas ; Stoop, Pieter ; Thijs, Peter ; Toebosch, Moniek ; Verdult, Dick ; de Weyer, Tine van
biog. per kunstenaar
Nederlands
Brabant BIënnale, Van Abbemuseum, Eindhoven / De Beyerd, Breda / Kultureel Sentrum, Tilburg / Het Markiezenhof, Bergen op Zoom / 't Meyhuis, Helmond, 12 sept. tm 12 okt. 1980
boek
Keywords: Brabant